A characterization of irreducible infeasible subsystems in flow networks. Issue 2 (28th June 2016) - Joormann, Imke; Orlin, James B.; Pfetsch, Marc E.
Abstract : Infeasible network flow problems with supplies and demands can be characterized via violated cut‐inequalities of the classical Gale‐Hoffman theorem. Written as a linear program, irreducible infeasible subsystems (IISs) provide a different means of infeasibility characterization. In this article, we answer a question left open in the literature by showing a one‐to‐one correspondence between IISs and Gale‐Hoffman‐inequalities in which one side of the cut has to be weakly connected. We also show that a single max‐flow computation allows one to compute an IIS. Moreover, we prove that finding an IIS of minimal cardinality in this special case of flow networks is strongly N P ‐hard. © 2016 Wiley Periodicals, Inc. NETWORKS, Vol. 68(2), 121–129 2016